Bottom up approaches for amino β-CD adsorption on gold surfaces. A comparative study. (10th June 2016) - García, Marycarmen; Bollo, Soledad; Rivas, Gustavo A.; Ferreyra, Nancy F.; Yáñez, Claudia
Abstract: The immobilization of three amino-β-cyclodextrin derivatives on gold surfaces via different bottom-up approaches was evaluated using cyclic voltammetry and surface plasmon resonance. Direct adsorption on gold and covalent attachment via amide bond formation with carboxylic groups of both the self-assembled monolayer of 4-mercapto benzoic acid (4-MBA) and the electrografted diazonium salt synthesized in situ from 4-amino benzoic acid (4-ABA) were tested. Amino β-CD with 1, 2 or 7 amine groups on the primary rim were used. The influence of the immobilization methodologies on the electrochemical properties of the resulting surfaces was studied using hydroquinone and ferricyanide as redox probes. The results indicate that the surface coverage of the molecules as well as their organization at the gold substrate depends on the number of amine groups on the primary rim of β-CD. A higher coverage via direct adsorption is obtained using the 7-amino groups derivative, while the highest coverage is reached with the 2-amino groups derivative via covalent attachment at diazonium salt electrografted surfaces. A critical discussion about the influence of different strategies used for the immobilization and the number of terminal amine groups on the β-CD structure is performed.